Connecting the dots: The role of internationally mobile scientists in linking nonmobile scientists with foreign scientists - Rodrigo Ito; Diego Chavarro; Tommaso Ciarli; Robin A. Cowan; Fabiana Visentin (Inter-American Development Bank (IDB), 2024)
Studying and working abroad, internationally mobile scientists meet foreign scientists and become carriers of knowledge. The benefits of international scientific mobility might extend to nonmobile colleagues who collaborate with mobile scientists. In this paper, we investigate the role played by Brazilian and Colombian scientists who are mobile in connecting nonmobile scientists with foreign scientists. We combine publicly available data from online curriculum vitae (CVs), scholarship programs, and publications in OpenAlex. We analyze a large sample covering approximately 70 percent of scientists for both countries and their coauthorship networks between 1990 and 2021, combining panel estimations and a difference-in-differences (DiD) event study. We find that nonmobile scientists who coauthor with mobile scientists coauthor more publications with foreign scientists. The number of collaborations by nonmobile scientists with foreign scientists increases with the number of unique mobile scientists the nonmobile scientists interact with. This is because the effect of collaborating with a unique mobile scientist is short-lived. Results suggest that mobile scientists who stay abroad more (diaspora) may be the most effective in creating connections with foreign scientists. Our paper contributes to the literature on scientific mobility and brain drain. We provide first insights into the spillover generated by mobility experiences in connecting nonmobile scientists with foreign scientists. Our results indicate a need to increase brain gain and reduce brain drain from home countries by increasing the links between mobile scientists and nonmobile scientists.
Keywords: O15; O3; D83; 330; international scientific mobility; coauthorship networks; social capital spillovers; Colombia; Brazil